Rubidium doped zeolite rho: structure and microwave conductivity of a metallic zeolite. - Anderson, P; Armstrong, A; Barker, P; Edmondson, M; Edwards, P; Porch, A (2004)
Large crystallites of high purity zeolite rho were synthesized by controlled monitoring of the aging and heating period of the mother gel. The microwave conductivity of Rb-rho doped with up to 20 Rb atoms per unit cell was measured over the temperature range 15-300 K, and the structures of three of the samples were examined through Rietveld analysis of powder neutron diffraction data. At low concentrations of rubidium dopant the observed microwave responses were dominated by polarization effects. In the sample Rb(17)/Rb-rho a strongly temperature-dependent electronic contribution to the conductivity was observed above approximately =150 K. In Rb(20)/Rb-rho, conductivities in the range 1.5-2.3 Sm(-1) were observed between 15 and 300 K. This residual conductivity at 15 K, unprecedented in a zeolite, indicates that the sample is indeed metallic; however, the values of conductivity measured are low in comparison to conventional metals and comparable to those of doped semiconductors. The evolution of the conducting behaviour is discussed in relation both to observed structural and to possible electronic changes occurring within the samples on metal doping.